The Foundation's Leadership Strategy for Developing Nurul Mannan Elementary School in West Banjar Gapura Sumenep - Ahmad Shiddiq; muhammad Misbahudholam AR (Universitas Muhammadiyah Enrekang, 2022)
The research aims to illustrate the role of the Nurul Mannan Foundation to develop schools in Ma'arif Nurul Mannan Elementary School and Describe and analyze the leadership strategy of the Nurul Mannan Foundation for School Development in Ma'arif Nurul Mannan Elementary School.This research uses a qualitative approach with a multi-case study, with naturalist phenomenological methods. The presence of researchers since 2021 is carried out intensively. Human and nonhuman data sources are unearthed with field observations, in-depth interviews and dukumentation. Data analysis uses Mile Huberman saldana theory through three stages, namely Data Condensation (Condensation), Data Offering, and Conclusion/verification withdrawal. Checking the validity of the data obtained is done by showing the degree of trust (credibility), transferability, dependency (dependability), and certainty (confirmability). The leadership role of nurul manann foundation in developing schools in Ma'arif Nurul Mannan elementary school is as a communicator between stake holder networks, as well as a strategic policy maker in the development of education in the auspices of the Nurul Mannan Banjar Barat foundation. In addition, the leadership strategy of the Nurul Mannan Foundation in developing the School at Ma'arif Nurul Mannan Elementary School by using strategic and tactical steps. Where these measures have logical consequences for the development of Ma'arif Nurul Mannan elementary school with measurable and can be evaluated properly.